Anti Obesity and Lipid - Lowering Effect of Lactobacillus Spp. as Probiotic on the Obese Rat. - AL-Ajeeli, Fakhri; Flayyih, May; Alkhazrajy, Lujain (Iraqi Journal of Science, 2023)
The effects of Lactobacillus acidophilus, Lactobacillus plantarum, Lactobacillus casiand Lactobacillus rhomunas on the body weight and lipid metabolism on obese ratswere evaluated. In the body weight, the results showed significant deferencebetween rat groups, the group that consumed 3 probiotic strains showed reduction inthe body weight with ratio 16.63% while the group consumed 2 probiotic strainsshowed decreasing with ratio 17.62% compared with control group which increasedin the body weight.In the effeci of probiotics on lipid metabolisim the resultsshowed significant deference between rat groups, the group that consumed 3probiotic strains showed decreasing in the cholesterol with ratio 50.7%, triglyceridewith ratio 48.8 %, LDL with ratio 51% and elevated of HDL level with ratio 45%,while the group consumed the 2 probiotic strains showed decreasing in thecholesterol with ratio 48.3%, triglyceride with ratio 43.3 %, LDL with ratio 27.4%and elevated HDL level with ratio 26%. The study suggests that LABsupplementation has hypocholesterolemic and anti obesity effects in rats. Thesestrains might be able to improve the intestinal microbial balance and potentiallyimprove intestinal transit time.